2009
DOI: 10.1038/eye.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodialysis on intraocular pressure

Abstract: Aims To study the effect of haemodialysis on intraocular pressure (IOP) of patients at the University Malaya Medical Centre, Kuala Lumpur, and the influence of anterior chamber angles, surgery, and diabetes on the change in IOP after haemodialysis. Methods Prospective, single centre study on patients undergoing haemodialysis with a sample size of 98 eyes (49 patients). Ocular examination was performed before haemodialysis. Pre-and post-haemodialysis IOP measurements were taken. Plasma osmolarity changes and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…17 The removal of water during HD decreases plasma volume and the concentration of plasma proteins increase; this increase in colloid osmotic pressure draws water from the aqueous humor into plasma. 9,16 In the present study there was a significant decrease in IOP during HD (from 16.71 ±2.51 at pre-HD to 15.52 ±3.18 at end-HD), which might have been due to the improvement in HD techniques since the time the earlier studies were performed. Slower HD may prevent abrupt changes in mOsm, and fluid shift to the eyes may be limited.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…17 The removal of water during HD decreases plasma volume and the concentration of plasma proteins increase; this increase in colloid osmotic pressure draws water from the aqueous humor into plasma. 9,16 In the present study there was a significant decrease in IOP during HD (from 16.71 ±2.51 at pre-HD to 15.52 ±3.18 at end-HD), which might have been due to the improvement in HD techniques since the time the earlier studies were performed. Slower HD may prevent abrupt changes in mOsm, and fluid shift to the eyes may be limited.…”
Section: Discussionmentioning
confidence: 55%
“…6 During HD, an increase in colloid osmotic pressure draws water from the aqueous humor into plasma. 9,16 In the present study, the effect of elevated colloid osmotic pressure on IOP might have been greater than the effect of the decrease in mOsm on IOP, which is why HD led to lower IOP values. Despite the reported marked rise in IOP, in the present study there was a 1.2 mm Hg of IOP decrease during HD, which is also comparable with the study conducted by Tokuyama.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…6 13 found that anterior chamber depth (ACD) significantly decreased during HD, whereas axial length (AL) remained unchanged. It can be summarized that a clearness regarding the effect of HD on ocular biometric parameters and intraocular power calculation, which is calculated by using biometric parameters has not yet been reached.…”
Section: Introductionmentioning
confidence: 99%
“…previously published studies appear inconsistent [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][23][24][25][26][27]. This may be attributed to the methodological differences, such as different exclusion criteria, variable sample size and different tonometry techniques and possibly due to significant technical progress in the HD procedure itself over the years [28].…”
Section: Association Of Iop and Hd-clinical Studiesmentioning
confidence: 80%